Caregivers of Schizophrenia Patients - Kerime Bademli; Zekiye Cetinkaya Duman (Psikiyatride Güncel Yaklaşımlar, 2013)
Most schizophrenia patients live with their families and therefore the mental illnesses adversely affects family members as well as the patients. Family members often experience a number of challenges in providing care. They have been reported to have certain emotional difficulties such as anxiety, depression, shame, sense of guilt, fear, helplessness, uneasiness, distress, despair, anger and sense of loss. Family members have to cope with such complications on their own in most cases. However, in some cases, family members may fail to deal with such emotional strains and experience psychological problems. It is considered to be highly important to identify challenges anddifficulties that family members may encounter and implement effective measures.